PHYTOTHERAPY FOR ENDOMETRITIS AND SUBSEQUENT CONCEPTION RATE IN REPEAT BREEDING CROSSBRED COWS - RAHI, S; GUPTA, H P; PRASAD, SHIV; BAITHALU, R K (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to study the comparative effect of herbal extract of garlic (crude) and ashwagandha (hydro-ethanolic) with antibiotic ciprofloxacin for the treatment of endometritis and repeat breeding condition in cross bred cows. Sixty four repeat breeding cross bred cows with endometritis were divided into eight groups and treated with PBS, antibiotic ciprofloxacin Ashwagandha 1/U, garlic 1/U, ashwagandha oral, ashwagandha oral+ garlic 1/U ashwagandha + garlic 1/U, ashwagandha oral+ 1/U, respectively at estrus. At subsequent estrus after treatment, majority of cows treated with herbal extracts and antibiotic showed better recovery rate evidenced on the basis of clear mucus discharge, negative reaction to white side test, reduction in bacterial load in cervical mucus. Better conception rate was observed in ashwagandha + garlic group at par with ciprofloxacin treated group due to their synergistic effect in combating infection and good immunomodulatory properties (Mishra et al., 2000) as compared to control, where no animal became pregnant. On the basis of present investigation, it is concluded that garlic+ ashwagandha extract (Group-G) was found as the most effective treatment among all treated groups and, thus, can replace conventional antibiotic in future for bacterial endometritis leading to repeat breeding condition in cross bred cows.